Pengaruh Pengetahuan dan Kepatuhan Terhadap Keselamatan dan Kesehatan Kerja pada Shop Packing PT. Yamaha Indonesia Motor Manufacturing - Dika Ariyatna; Enjang Suherman; Laras Ratu Khalida (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the effect of knowledge and compliance on K3. This research was carried out at PT Yamaha Indonesia Motor Manufacturing West Java. The research method is descriptive quantitative verification with multiple linear regression analysis using SPSS25 calculations. The population consists of employees of at the packing shop, totaling 102 individuals. Using Slovin's formula with a 5% significance level, 81 respondents were selected. The sampling method applied random sampling techniques based on the criteria for permanent and contract employees. Based on the research results, it can be concluded that, knowledge with a score of 200 is in the high category, compliance with a score of 174 is quite high, while, K3 with a score of 206 is in the good category, knowledge partially has a very significant positive effect with a sig value of 0.001 < 0.05 while tcount is 4.813 > from t table 1.988 on K3, compliance has a very significant positive effect with a sig value of 0.000 < 0.05 while tcount is 3.154 > T table 1.988 towards K3, Simultaneously, knowledge and compliance have an effect on K3 with a sig value of 0.000 < 0.05 and fcount 93,078 > f table 3.09. Meanwhile, the determination value is 0.751 or 75.1%, while the remaining 0.239 or 23.9% is the contribution of other variables not examined in this research.